Energy absorption and Poisson's ratio of warp-knitted spacer fabrics under uniaxial tension. Issue 6 (March 2019) - Chang, Yuping; Ma, Pibo
This paper presents five different auxetic warp-knitted spacer fabrics and discusses their energy absorption under uniaxial tension through integrals of stress on strain. Structures of auxetic fabrics are designed based on rotating hexagonal models and knitted for experimental tests, including Poisson's ratio tests and tensile tests. Results show that energy absorption of auxetic warp-knitted spacer fabric is mainly determined by its structural deformation capacity and yarn loading capacity, between which the yarn loading capacity of fabrics plays the dominant part in energy absorption, while the structural deformation capacity, which is affected by Poisson's ratio, has relatively little influence. With equivalent yarn loading capacity, the energy absorption of fabrics with negative Poisson's ratios are relatively better.